Peter and the North Wind - Littledale, Freya, 1929-; Howell, Troy (New York : Scholastic, 1988)
The North Wind's magical gifts to Peter, recompense for blowing away the flour needed to feed him and his poor mother, mysteriously lose their magic before Peter gets them home.
"Retold from the Norse tale The lad who went to the North Wind."
2.5
K-3
Keywords: Folklore -- Norway; Folklore